PERANAN FOSIL UNTUK MENGETAHUI SEJARAH BUMI DAN PERADABAN MASA LAMPAU ( Sosialisasi Ilmu Geologi Bagi Guru-guru Sejarah) - Jusfarida Jusfarida; Handoko Teguh Wibowo; Diah Wully Agustine; Aleik Ainu Abdilbar (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
The role of fossils in determining the history of the earth and civilizations is very important, especially to find out the age of rocks containing oil and natural gas, minerals, the history of deposition and raise and fall of sea level and to reveal past times that have changed human civilization, such as the occurence of disasters that demolish a civilization and others. Geological studies to determine the geological age related to history of the earth and past civilizations using index fossils. The index fossils is a characteristic of organisms that lived a certain time, so that the fossils index in a rock layes can be used to determine age of rocks. Another function of fossils is to determine the depositional environment, ancient currents, and climate in the area where the organism lives. Fossils analysis can also be used to determine the catastrophic events that occurred in the past. The study of history of civilization is closedly related to the field of historical science that focused more on past lives. Lately, many sites have been found from the relics of the past, where the sites is the key to knowing past living conditions. The results of the analysis of the age of the site (eg. Temple) can be matched with the historical periods of disaster occurrence and the collapse of a civilization due to disaster. So that collaboration between geologist and historians (Archeology) is expected to be able to synergize the two fields of science in uncovering past events, such as seismic history, tsunami history, paloegeography, etc. Which then become a reference in kowing the causes of the collapse of the past empire.Keyword: Earth’s history, past life, Fossils